IgE mediated sensitisation to aeroallergens in an asthmatic cohort: relationship with inflammatory phenotypes and disease severity. Issue 7 (28th June 2016) - Manise, M.; Bakayoko, B.; Schleich, F.; Corhay, J.‐L.; Louis, R.
Summary: Background: Atopy is known to play an important role in the asthmatic disease. The main objective of this study was to evaluate the frequency of sensitisation to common aeroallergens in a cohort of asthmatics with different inflammatory phenotypes and disease severity. Methods: We have conducted a retrospective cross‐sectional study including 772 asthmatics recruited between 2003 and 2014 in our Asthma Clinic. The patients were defined as asthmatics on the basis of respiratory symptoms together with a positive methacholine test (PC20M) < 16 mg/ml and/or a reversibility to short‐acting β2‐agonists (salbutamol) ≥ 12% and 200 ml. Sensitisation to house dust mites, grass and birch pollens, cats, dogs and moulds was assessed by RAST and a specific immunoglobulin E (IgE) > 0.35 kU/l was considered as significant. Inflammatory phenotypes were subdivided between pauci‐granulocytic ( n = 309) (40%), eosinophilic ( n = 311) (40%), neutrophilic ( N = 134) (17%) and mixed‐granulocytic ( N = 18) (3%) asthmatics. Severe asthmatics ( n = 118) were defined according to the American Thoracic Society (ATS 2000) criteria and compared with mild‐to‐moderate asthmatics ( N = 654). Results: The eosinophilic phenotype was associated with higher levels of total serum IgE compared with neutrophilic and pauci‐granulocytic asthma (p < 0.001 for both). Sensitisation rate to dogs and cats was higher in eosinophilic asthmatics (31% and 37%, respectively, p < 0.01 both) compared with neutrophilic (18% and 23% respectively) and pauci‐granulocytic asthmatics (20% and 24%, respectively), while sensitisation rate to house dust mites and moulds were rather similar between the groups (ranging from 33% to 40% and from 10% to 16%, respectively). Severe asthmatics had slightly increased total serum IgE compared with mild‐to‐moderate asthmatics (p < 0.05) without any difference in the sensitisation rate to common aeroallergens. Conclusion: Eosinophilic asthma exhibits higher total serum IgE and sensitisation rate towards animal dander while clinical severity, though also associated with higher total IgE, did not preferentially relate to any type of common aeroallergens.